Antigen Presenting Cells Link the Female Genital Tract Microbiome to Mucosal Inflammation, With Hormonal Contraception as an Additional Modulator of Inflammatory Signatures - Byrne, Elizabeth H.; Farcasanu, Mara; Bloom, Seth M.; Xulu, Nondumiso; Xu, Jiawu; Hykes, Barry L.; Mafunda, Nomfuneko A.; Hayward, Matthew R.; Dong, Mary; Dong, Krista L.; Gumbi, Thandeka; Ceasar, Fransisca Xolisile; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The microbiome of the female genital tract (FGT) is closely linked to reproductive health outcomes. Diverse, anaerobe-dominated communities with low Lactobacillus abundance are associated with a number of adverse reproductive outcomes, such as preterm birth, cervical dysplasia, and sexually transmitted infections (STIs), including HIV. Vaginal dysbiosis is associated with local mucosal inflammation, which likely serves as a biological mediator of poor reproductive outcomes. Yet the precise mechanisms of this FGT inflammation remain unclear. Studies in humans have been complicated by confounding demographic, behavioral, and clinical variables. Specifically, hormonal contraception is associated both with changes in the vaginal microbiome and with mucosal inflammation. In this study, we examined the transcriptional landscape of cervical cell populations in a cohort of South African women with differing vaginal microbial community types. We also investigate effects of reproductive hormones on the transcriptional profiles of cervical cells, focusing on the contraceptive depot medroxyprogesterone acetate (DMPA), the most common form of contraception in sub-Saharan Africa. We found that antigen presenting cells (APCs) are key mediators of microbiome associated FGT inflammation. We also found that DMPA is associated with significant transcriptional changes across multiple cell lineages, with some shared and some distinct pathways compared to the inflammatory signature seen with dysbiosis. These results highlight the importance of an integrated, systems-level approach to understanding host-microbe interactions, with an appreciation for important variables, such as reproductive hormones, in the complex system of the FGT mucosa.